2016
DOI: 10.5194/angeo-34-985-2016
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint spacecraft observations of long-lasting poloidal Pc4 pulsations in the dayside magnetosphere on 1–2 May 2014

Abstract: Abstract. We use magnetic field and plasma observations from the Van Allen Probes, Time History of Events and Macroscale Interactions during Substorms (THEMIS) and Geostationary Operational Environmental Satellite system (GOES) spacecraft to study the spatial and temporal characteristics of long-lasting poloidal Pc4 pulsations in the dayside magnetosphere. The pulsations were observed after the main phase of a moderate storm during low geomagnetic activity. The pulsations occurred during various interplanetary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
1
13
0
3
Order By: Relevance
“…One category of poloidal ULF waves is characterized by their long lifetime from several hours to days (e.g., Korotova et al, ; Le et al, ; Sarris et al, ). Most previous studies on the long‐lasting poloidal ULF waves were focused on wave properties in the magnetosphere (Korotova et al, ; Le et al, ; Min et al, ; Takahashi et al, ). Interestingly, the waves were usually monochromatic and observed during low geomagnetic activity after a geomagnetic storm or within the storm recovery phase, as summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…One category of poloidal ULF waves is characterized by their long lifetime from several hours to days (e.g., Korotova et al, ; Le et al, ; Sarris et al, ). Most previous studies on the long‐lasting poloidal ULF waves were focused on wave properties in the magnetosphere (Korotova et al, ; Le et al, ; Min et al, ; Takahashi et al, ). Interestingly, the waves were usually monochromatic and observed during low geomagnetic activity after a geomagnetic storm or within the storm recovery phase, as summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies discussing excitation of poloidal waves by the drift‐bounce resonance (e.g., Anderson et al, ; Engebretson et al, ; Hughes et al, ; Kokubun et al, ; Korotova et al, ; Liu et al, ; Min et al, ; Takahashi et al, ). Large‐m poloidal waves are thought to be excited by the drift‐bounce resonance mechanism associated with hot ring current protons (Anderson et al, ; Kokubun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Zong et al [2009] studied shock-excited waves using nine satellites and observed both poloidal and toroidal waves with comparable intensity at L = 4.4, but only toroidal waves at geosynchronous orbit. Korotova et al [2016] observed poloidal waves that occurred simultaneously over a local time extent of~10 h during the recovering phase of a magnetic storm. In this paper, we report a rare example in which storm time high-m poloidal waves are observed globally by 15 satellites from five missions including Magnetospheric Multiscale (MMS), Van Allen Probes, Time History of Events and Macroscale Interactions during Substorm (THEMIS), Cluster, and Geostationary Operational Environmental Satellites (GOES), covering L values between~4 and 12 as well as local times from the morning, noon, afternoon, and postdusk local time sectors.…”
Section: Introductionmentioning
confidence: 99%